Understanding Determinants of Carbohydrate Metabolism and Their Contribution to Metabolic Health; The Impact of AMY1 CNV (P21-015-19) - O'Callaghan, Nathan (Curr Dev Nutr, 2019)
OBJECTIVES: Salivary α- amylase (AMY1) is responsible for the breakdown of starch into oligosaccharides, tri and di-saccharides giving a start to the starch digestion in the oral cavity on food consumption. Several studies recently reported contradicting results regarding the link between AMY1 copy numbers (CNs) and obesity and type 2 diabetes. Objective: We investigated whether CN in the AMY1 gene was associated with differential anthropometrics and glycaemic outcomes in obese individuals who underwent a dietary plan varying in macronutrient intake, as a part of weight loss and weight maintenance program. We also investigated whether there existed an interaction between nutrient intakes and AMY1 CNs and if AMY1 CNs have influence on body weight, body composition and glycemic trajectories during dietary interventions. METHODS: Using the Paralogue Ratio Test, we accurately measured the AMY1 CNs in 761 obese individuals from the Diogenes study. Subjects underwent first an 8-week low-caloric diet (LCD, at 800 kcal/d) and those achieving >8% weight loss were then randomized to a 6-month weight maintenance dietary (WMD) intervention. The association between AMY1 CNs and weight- and glycemic- parameters was tested at baseline and following each intervention phase (LCD, WMD) with the use of linear mixed effect models adjusting for gender, age, center and total energy intake. RESULTS: At baseline, a modest association between AMY1 CN and BMI (P = 0.04) was observed. AMY1 CN was not associated with baseline glycemic variables. Additionally, AMY1 CN was not associated with anthropometric or glycemic-outcomes following either LCD or WMD. Interaction analyses between AMY1 CN and nutrient intake did not reveal significant association with any clinical parameters (at baseline and following LCD or WMD) or when testing gene x WMD interactions during the WMD phase CONCLUSIONS: In the absence of association with weight trajectories or glycemic improvements, the AMY1 CN cannot be considered as an important biomarker for response to a clinical weight loss and weight maintenance programs in overweight/obese subjects. FUNDING SOURCES: European Commission, Food Quality and Safety Priority of the Sixth Framework Program (FP6-2005-513946), Nestlé Institute of Health Sciences. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.